The Kerepeks / Muhammad Anas Zamzuri - Zamzuri, Muhammad Anas (2021)
Our chips brand, The Kerepeks, is the name of our products. The major purpose of the company is to present our consumers with a variety of flavour options rather than providing them with a single flavour at a low cost. This company has been in operation for a year. According to customer reviews, this product has an excellent taste since the various flavours help our consumers recall the taste. This product is very affordable and easily available. As a result, this product suggests that our clients' sales have a bright future. The Kerepeks have sold over ten bottles in a variety of flavours, including cheese, chocolate, and nestum, since its debut. Increased demand for our products was a result of profitable sales for our firm initiatives. As a result, The Kerepeks is a product of choice, with the potential to be marketed and developed into other industries as the company grows.